A Community Health Approach to Asthma in the Schools - Weiss-Randall, Debra (Kappa Delta Pi record, 2014)
Asthma is a leading cause of school absenteeism in the United States, especially in poor and minority communities, where prevalence and hospitalization rates are significantly higher than average. A community health approach can help poorer school districts hire full-time nurses and access other health resources.